2021
DOI: 10.1302/2633-1462.26.bjo-2021-0017.r1
|View full text |Cite
|
Sign up to set email alerts
|

Osteointegration of hydroxyapatite-coated collars in cemented massive endoprostheses following revision surgery

Abstract: Aims Hydroxyapatite (HA)-coated collars have been shown to reduce aseptic loosening of massive endoprostheses following primary surgery. Limited information exists about their effectiveness in revision surgery. The aim of this study was to radiologically assess osteointegration to HA-coated collars of cemented massive endoprostheses following revision surgery. Methods Retrospective review of osseointegration frequency, pattern, and timing to a specific HA-coated collar on massive endoprostheses used in revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
0
9
2
Order By: Relevance
“…A recent study observed osseointegration around HA-coated collars in megaprostheses in less than half of reviewed cases [2]. Previous implant failure due to aseptic loosening, arguably the indication that would benefit most from collar osseointegration, was associated with an even worse ongrowth rate with the percentage dropping down to 27% [2]. Evolution of additive manufacturing technology not only allowed for emergence of custom-made patientspecific implants but also facilitated the incorporation of highly complex materials and surfaces in implant design and production processes [13,14].…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent study observed osseointegration around HA-coated collars in megaprostheses in less than half of reviewed cases [2]. Previous implant failure due to aseptic loosening, arguably the indication that would benefit most from collar osseointegration, was associated with an even worse ongrowth rate with the percentage dropping down to 27% [2]. Evolution of additive manufacturing technology not only allowed for emergence of custom-made patientspecific implants but also facilitated the incorporation of highly complex materials and surfaces in implant design and production processes [13,14].…”
Section: Introductionmentioning
confidence: 97%
“…In complex revision arthroplasty and orthopaedic oncology, a commonly used mode of reconstruction is endoprosthetic replacement using megaprostheses [1,2]. Despite recent advancements in implant design and refinements of implantation techniques resulting in improved prosthesis survival rates, tumour prosthesis remain associated with high complication and revision rates [1,2]. Available literature demonstrates all-cause revision rates of more than 40% in the first 10 years after implantation [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations